Allulose in human diet: the knowns and the unknowns. Issue 2 (28th July 2022) - Daniel, Hannelore; Hauner, Hans; Hornef, Mathias; Clavel, Thomas
Abstract: D-Allulose, also referred to as psicose, is a C3-epimer of D-fructose used as a sugar substitute in low energy products. It can be formed naturally during processing of food and drinks containing sucrose and fructose or is prepared by chemical synthesis or via enzymatic treatment with epimerases from fructose. Estimated intakes via Western style diets including sweetened beverages are below 500 mg per d but, when used as a sugar replacement, intake may reach 10 to 30 g per d depending on the food consumed. Due to its structural similarity with fructose, allulose uses the same transport and distribution pathways. But in contrast to fructose, the human genome does not encode for enzymes that are able to metabolise allulose leading to an almost complete renal excretion of the absorbed dose and near-to-zero energetic yield. However, in vitro studies have shown that certain bacteria such as Klebsiella pneumonia are able to utilise allulose as a substrate. This finding has been a subject of concern, since Klebsiella pneumoniae represents an opportunistic human pathogen. It therefore raised the question of whether a high dietary intake of allulose may cause an undesirable growth advantage for potentially harmful bacteria at mucosal sites such as the intestine or at systemic sites following invasive infection. In this brief review, we discuss the current state of science on these issues and define the research needs to better understand the fate of allulose and its metabolic and microbiological effects when ingested as a sugar substitute.